APPLICATION OF THE FIRST COME FIRST SERVED METHOD IN A WEB-BASED MARRIAGE REGISTRATION SYSTEM - Tenriangka Tenri; lilis Nur Hayati; Amaliah Faradibah Amaliah (Jurnal Riset Informatika, 2026)
Marriage registration at the Office of Religious Affairs (KUA) is still largely carried out using conventional methods, which gives rise to various problems such as document accumulation, the risk of file loss, data recording errors, and delays in the verification process, particularly for prospective couples who live far from the KUA office. This process requires prospective couples to visit the KUA office in person and submit physical documents, making it inefficient and ineffective. This study aims to develop a website-based marriage registration system that facilitates online registration for prospective couples and regulates the service order in an orderly and fair. This study applies the First Come First Served (FCFS) method to regulate the order of marriage registration based on the time of registration, ensuring a fair and orderly service process. Furthermore, the system development is carried out using the Waterfall approach, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The results show that the website-based marriage registration system operates according to the designed workflow. Alpha testing indicates that all main features function as specified, while beta testing obtained an average score of 4.18 with a percentage of 83.6%, which falls into the good category. These results indicate that the system is well accepted by users and suitable for implementation at the Office of Religious Affairs (KUA).